Combating human trafficking ın europe - Demir, Başak (My University, 2007)
Avrupa’da İnsan Ticareti ile Mücade adlı yüksek lisans tez çalışması Başak Demir tarafından gerçekleştirilmiştir. Bu çalışmada hedef Avrupa’da insan ticareti ile mücadele amacı ile geliştirilmiş müktesebatı incelemektir. Bu kapsamda Avrupa Birliği, Avrupa Konseyi ve Avrupa Güvenlik ve İşbirliği Teşkilatı işbirliğinde geliştirilmiş hukuki altyapı incelenmiştir. Bu tez çalışması insan ticareti suçunun uluslararası tanımı ile başlamaktadır. Tanımın gelişimi incelendikten sonra 2000 yılında Birleşmiş Milletler tarafından geliştirilen Palermo Protokolü ve 2002 İnsan Ticareti ile Mücadeleye Yönelik Avrupa Birliği Konseyi Çerçeve Kararı incelenmiştir. Suçun tanımı incelendikten sonra tezde Birleşmiş Miletler, Avrupa Birliği, Avrupa Konseyi ve Avrupa Güvenlik ve İşbirliği Teşkilatı tarafından geliştirilmiş politikalar ve yasal düzenlemeler incelenmiştir. Avrupa düzeyinde insan ticaretine yönelik geliştirilmiş müktesebatın incelenmesinin ardından tezde farklı Avrupa ülkelerindeki uygulamalar araştırılmıştır. Öncelikli olarak Avusturya, Belçika, Hollanda, İtalya, Çek Cumhuriyeti, Güney Kıbrıs Rum Kesimi, Bosna Hersek ve Rusya’daki uygulamalar genel olarak incelenmiş, ardından Türk Ceza Kanunu’ndaki maddeler üzerinde durulmuştur. Ayrıca Türkiye’de farklı kurumların insan ticareti ile mücadeleye yönelik geliştiridiği farklı projelere de yer verilmiştir. Tez çalışması insan ticareti ile mücadelenin güçlendirilmesine yönelik farklı strateji önerileri ile son bulmaktadır.

Combating Human Trafficking in Europe is a master thesis written by Basak Demir with an aim to analyze the European legal framework against trafficking in human beings established by the European Union in cooperation with the Council of Europe, and Organization for Security and Cooperation in Europe. The study begins with a focus on the definition of human trafficking that is established by various international instruments including the 2000 Trafficking Protocol to the United Nations Convention on Transnational Organized Crime and the 2002 Council Framework Decision on Combating Trafficking in Human Beings. After a brief analysis on the definition of the crime, Mrs. Demir further studies the legal instruments as well as the policy documents developed by the United Nations, the European Union, the Council of Europe and the Organization for Security and Cooperation in Europe. The evaluation of the European legal response to trafficking in human beings follows a thorough examination of the state practice in Europe. Briefly analyzing the legal framework and the practice in Austria, Belgium, the Netherlands, Italy, Czech Republic, Greek Administration of Southern Cyprus, Bosnia and Herzegovina and Russia, the study focuses on the articles that respond to the crime of human trafficking in the Turkish Penal Code. In addition, the study analyses different practices against trafficking in human beings in Turkey. The study concludes with proposals for different tools and strategies to be established for the fight against trafficking in human beings.
Keywords: Avrupa Birliği Hukuku; İnsan Ticareti_Avrupa Birliği